Pengaruh Kualitas Interaksi Penjual-Pembeli dan Atmosfer Pasar Tradisional Terhadap Minat Berkunjung Kembali Melalui Pengalaman Berbelanja - Wiranatha I Gusti Putu Satrya; Luh Putu Mahyuni (eCo-Buss, 2025)
This study investigates the influence of seller-buyer interaction quality and traditional market atmosphere on revisit intention, mediated by shopping experience. Conducted in four traditional markets in Denpasar, Bali, this research adopts a quantitative approach using a closed-ended questionnaire distributed to 100 purposively selected respondents. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results demonstrate that both seller-buyer interaction and market atmosphere significantly influence shopping experience and revisit intention. Furthermore, shopping experience plays a mediating role in strengthening the effect of market atmosphere on revisit intention. These findings support the Stimulus-Organism-Response (S-O-R) framework, indicating that external stimuli (interaction quality and atmosphere) affect internal responses (shopping experience), which subsequently influence behavioural outcomes (revisit intention). The study highlights the importance of enhancing interpersonal service quality and environmental factors in traditional markets to foster consumer loyalty. Practical implications include the need for revitalization strategies that integrate emotional engagement and experiential values to increase competitiveness amid modern retail growth. This study contributes to the limited literature that simultaneously examines interaction quality, market atmosphere, and revisit intention through a mediated consumer behaviour model within the context of local traditional markets.